Diagnosis of the current situation of the cemeteries in Cuiabá-MT from the perspective of environmental management: case study the Cemetery ParqueBom Jesus of Cuiabá and São Gonçalo Municipal - Xavier, Cléber Carmino; Amorim, Marleide Rodrigues; Valentini, Carla Maria Abido; Faria, Rozilaine Aparecida Pelegrine Gomes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The study was developed in order to make a diagnosis of the current situationof the cemeteries Parque Bom Jesus de Cuiaba and Sao Goncalo in the city of Cuiaba-MT, from the perspective of environmental management focusing on the number of bodies and on construction.The methodology used was the consultation documents that have historically shown the facilities of public cemeteries in the area and the governmental laws; data provided by the Central Municipal Funeral Services of the Municipality of Cuiabá-MT connected to Municipal Infrastructure and site visits. Major changes in the practice of burial in churches until the mid-nineteenth century in Cuiabá occurred due to necrochorume running down the tombs. Lawmakers needed, then write and enforce practices of postures as a way to mitigate the possible impacts of these improper practices of burial. The Federal Government began treating as an enterprise installation of cemeteries and demanded, since the licenses for them to operate, leaving the municipality for the same. It was concluded that contamination of the respective cemeteries would not be significant from the standpoint of the number of burials, but for a validation of this claim would require a constant monitoring of groundwater and soils of the sites, and it is necessary, as provided in Law who obtain operating licenses